DETERMINATION OF KINETIC PARAMETERS FOR OPEN SCHIFF BASES DEPENDING ON EXTRACTION TECHNIQUE - Kandil, Farouk; Falah, Ahmad; Essa, Hameed (Iraqi Journal of Science, 2024)
This work was focused on the preoarated of tetradentate Schiff baseswhich were prepared by condensation of terephtalaldehyde and diPhenyldialdehyde with 2-amino phenol. The Schiff base ligands were identified bydifferent spectral technique (GC-MS, 1H-NMR, IR).The influences ofshaking time on the extraction of Cu (II) using solvent extraction techniquewas studied. Kinetic parameters [(n) reaction order